2-Mercaptobenzimidazole-functionalized chitosan for enhanced removal of methylene blue: Batch and column studies. Issue 4 (August 2021) - Elwakeel, Khalid Z.; Elgarahy, Ahmed M.; Al-Bogami, Abdullah S.; Hamza, Mohammed F.; Guibal, Eric
Abstract: Chitosan functionalized with 2-mercaptobenzimidazole (2-MBI) (i.e. 2-MBI@Chit) shows high sorption capacity (i.e., 1.28 mmol MB g −1 ) for methylene blue (MB) (at pH close to 9.3). Sorption is weakly decreased (by less than 25%) by high NaCl concentration (up to 45 g L −1 ). The sorption (slightly endothermic) is fitted by the Langmuir equation. The kinetic profile is fitted by the pseudo-first order rate equation (PFORE): equilibrium reached within 90 min of contact. The resistance to film diffusion is minimized when setting agitation speed at 200 rpm. Dye desorption is successfully achieved (up to 94.5%) using 0.8 M HCl; desorption kinetics is little slower than the sorption step. The loss in sorption capacity at the fifth sorption/desorption cycle does not exceed 5%. Yoon–Nelson, Bohart–Adams, and bed-depth service time equations are used for analyzing the breakthrough in fixed-bed columns. At the exhaustion of the column, the sorption capacity approaches the maximum sorption capacity in batch: all the reactive groups remain accessible in dynamic sorption mode. The dye is efficiently recovered from spiked seawater and the sorption performance is depreciated by less than 16% while comparing tap water and seawater under selected experimental conditions. Graphical Abstract: ga1 Highlights: Methyl benzimidazole/chitosan for efficient sorption of methylene blue. Maximum sorption capacity close to 1.28 mmol g −1, fitted by Langmuir equation. Fast kinetics (equilibrium ~ 90 min), fitted by pseudo-first order rate equation. Dye elution by 0.8 M HCl solution; sorption stability over 5 cycles (loss < 5%). Efficient modeling of breakthrough curves in columns by the Yoon–Nelson equation.